2013
DOI: 10.4183/aeb.2013.41
|View full text |Cite
|
Sign up to set email alerts
|

Application of immunohistochemical markers in the differential diagnosis of thyroid tumors

Abstract: Aim.To evaluate the expression of Galectin-3, Fibronectin-1, Cytokeratin-19 and HBME 1 in benign and malignant thyroid nodules and to assess their diagnostic value.Methods. Immunohistochemical analysis was performed on 59 surgically removed thyroid nodules, including 34 carcinomas (12 papillary, 2 tall cell variants, 3 lymph node metastases from papillary carcinoma, 5 follicular variants of papillary carcinoma (FVPTC), 3 anaplastic, 5 follicular and 4 Hürthle cell carcinomas), as well as 25 benign lesions (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However the lack of immunostaining for other markers for the assessment of the tumoral profile is a limitation of this report. Immunohistochemistry is beneficial not only in differentiating benign from malignant thyroid lesions, but it also helps in better characterization of mixed thyroid tumors (15). Although our patient had significant improvement in clinical symptoms following I 131 therapy, long-term prognosis in her is guarded.…”
Section: Discussionmentioning
confidence: 96%
“…However the lack of immunostaining for other markers for the assessment of the tumoral profile is a limitation of this report. Immunohistochemistry is beneficial not only in differentiating benign from malignant thyroid lesions, but it also helps in better characterization of mixed thyroid tumors (15). Although our patient had significant improvement in clinical symptoms following I 131 therapy, long-term prognosis in her is guarded.…”
Section: Discussionmentioning
confidence: 96%
“…This result was similar to other studies. 10,11 Hanan Alsaeid Alshenawy, stated in his study that CK-19 is always positive in papillary carcinoma in contrast to other thyroid malignancies. He reported that all 14 cases of papillary carcinoma showed positivity with cytokeratin 19 comprising 100%.…”
Section: Discussionmentioning
confidence: 97%
“…The current study pointed that; the expression of CK19 in PTC including FVPTC was significantly higher than in other thyroid lesions including follicular neoplasms and hyperplastic nodules. Palo and Biligi and Siderova et al reported similar relation supporting that it can serve to differentiate PTC from follicular neoplasm [19,21]. However, other studies found higher expression of Ck19 in follicular neoplasm and hyperplastic nodules [18,20].…”
Section: Cd117 Expression (Dab Immunoperoxidase) (A) Negativity Withmentioning
confidence: 92%
“…In our study, we selected only those papillary thyroid carcinomas In our study, CK19 strongly immunoreacted with (87.5%) cases of PTC; while negative cases (3 cases) show focal immunoreactivity in less than 10% hence considered negative. As shown in Table 4 previous studies reported CK19 expression in most of their studied PTC cases, ranging from 75.9% to 100% [16][17][18][19][20][21].…”
Section: Cd117 Expression (Dab Immunoperoxidase) (A) Negativity Withmentioning
confidence: 99%